Information technology in the evaluation of technical efficiency in rhythmic gymnastics group event - Manos, M.; Popescu, L. (Science, Movement & Health, 2018)
Problem statement. Planning training in rhythmic gymnastics is a complex process aimed at achieving optimal sports performance. If the training analysis for the group event is pursued, many problems arise due to the large number of variables involved. Information technology makes available to the coach an efficient means of controlling the activity in terms of programming and in-depth evaluation of training, by facilitating the processing of a significant amount of data, the quick and objective analysis of recorded parameters and the graph visualisation. Purpose. To optimise the training in rhythmic gymnastics group event, we aimed to exploit the opportunities provided by computer programs and develop a training analysis method able to highlight at any moment the individual technical level of the gymnasts with reference to each element of the group exercise, the actual work performed during a technical training lesson and the number of errors for each difficulty element during the overall exercise. Method. For recording, processing and listing the data, an IBM laptop, a Windows-Excel program and an Epson Stylus C64 printer were used. Information was collected in the computer through the indirect method, namely it was entered by the observer, as the subjects` actions were being performed. This option allowed easy database manipulation and flexibility in combining, subdividing, rearranging and transforming the collected data. The measurement process included the recording of quantitative indicators, calculation of specific quantitative indicators and analysis of qualitative data. Results. Their analysis reveals that: 1. gymnasts achieve the best performances after 10-11 full repetitions of the competition routines; 2. there is a lack of constancy in the evolution of average scores for execution over a week; 3. the individual efficiency recorded over a week shows oscillations, better values being recorded at the end of the week, when the competitions are also scheduled. Conclusions. This method provides the opportunity to have a clear and objective vision of training, to monitor each gymnast, to compare her results with those of the group, to save much time, to intervene according to the situation.